High-energy-storage high-entropy ceramic dielectric material and preparation method thereof
By introducing a variety of A-position cations to construct high-entropy ceramics, combining the equilibrium of ferroelectric and non-ferroelectric phases, the problem of pure BaTiO3 poor performance in the energy storage field is solved, and a ceramic dielectric material with high energy storage density and efficiency is achieved.
Patent Information
- Application Number
- CN202411474160.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-17
AI Technical Summary
Pure BaTiO3 ceramics perform poorly in the energy storage field, mainly due to their large residual polarization characteristics. How to improve their performance by optimizing the structure has become an important issue.
High entropy ceramics were constructed by introducing six A-position cations (K, Na, Bi, Sr, Ca and Mg) to form Ba0.2[(K0.5Na0.5)Bi]x(SrCaMg)(2/3)( 0.4-x) TiO3 material combines the balance between ferroelectric and non-ferroelectric phases to optimize its energy storage performance.
The energy storage performance of ceramic dielectric materials is significantly improved, including narrow electrohysteresis loops and high breakdown field strength, while ensuring energy storage efficiency and achieving high energy storage density and efficiency.
Smart Images

Figure CN119320273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a high-energy storage and high-entropy ceramic dielectric material based on barium titanate and a preparation method thereof. Background Art
[0002] The concept of high entropy first came from high entropy alloys. Inspired by high entropy alloys, binary oxide (MgNiCoCuZn)O ceramics were successfully prepared in 2015. When it was discovered that it had a huge dielectric constant, high entropy ceramics were quickly applied to the field of energy storage. Since then, people have successively developed high entropy ceramics with different structures, such as perovskite, pyrochlore, spinel, etc. Among them, high entropy ceramics with perovskite structure have outstanding performance and have become a research hotspot.
[0003] BaTiO 3 BaTiO is a classic ceramic for large-scale capacitor manufacturing due to its high performance and low cost. 3 The large residual polarization characteristic is very unfavorable to its performance in energy storage. How to use the concept of "entropy engineering" to optimize its structure and improve its performance has become an important issue in its application in the field of energy storage. Summary of the invention
[0004] The present invention provides a high-energy storage and high-entropy ceramic dielectric material. Through the newly developed material composition, the dielectric material has a narrow hysteresis loop and a higher breakdown field strength, which greatly improves the energy storage performance while ensuring a certain energy storage efficiency.
[0005] The high energy storage and high entropy ceramic dielectric material provided by the present invention has the following chemical composition: Ba 0.2 [(K 0.5 Na 0.5 )Bi] x (SrCaMg) (2 / 3)(0.4-x) TiO 3 , where x = 0.16-0.20.
[0006] The method for preparing the high energy storage and high entropy ceramic dielectric material comprises the following steps:
[0007] (1) BaCO 3 , K 2 CO 3 、Na 2 CO 3 、Bi 2 O 3 、SrCO 3 、CaCO 3 MgCO 3 and TiO 2 Powders were used as raw materials, and the general formula BaTiO3 、CaTiO 3 、SrTiO 3 MgTiO 3 ,(K 0.5 Bi 0.5 )TiO 3 and(Na 0.5 Bi 0.5 )TiO 3 The ingredients were mixed, and then anhydrous ethanol was added to prepare the slurry. The powders were mixed evenly by ball milling, and then dried to remove the anhydrous ethanol to obtain BaTiO 3 、CaTiO 3 、SrTiO 3 MgTiO 3 ,(K 0.5 Bi 0.5 )TiO 3 and(Na 0.5 Bi 0.5 )TiO 3 Powder.
[0008] (2) Under closed conditions, CaTiO 3 、SrTiO 3 and MgTiO 3 The powder was pre-sintered at 860℃ to obtain CTO, STO and MTO raw materials; BaTiO 3 ,(K 0.5 Bi 0.5 )TiO 3 and(Na 0.5 Bi 0.5 )TiO 3 The powder is pre-sintered at 800°C to obtain BTO, KBT and NBT raw materials.
[0009] (3) The above CTO, STO, MTO, BTO, KBT and NBT raw materials are weighed according to the following mass ratio:
[0010] BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.16±10%):(0.16±10%):(0.16±10%):(0.08±10%):(0.08±10%);
[0011] Or BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.153±10%):(0.153±10%):(0.153±10%):(0.085±10%):(0.085±10%);
[0012] Or BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.1467±10%):(0.1467±10%):(0.1467±10%):(0.09±10%):(0.09±10%);
[0013] Or BTO:STO:CTO:MTO:KBT:NBT = (0.20 ± 10%): (0.14 ± 10%): (0.14 ± 10%): (0.14 ± 10%): (0.095 ± 10%): (0.095 ± 10%);
[0014] Or BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.133±10%):(0.133±10%):(0.133±10%):(0.10±10%):(0.10±10%).
[0015] Then, anhydrous ethanol is added, and a ceramic green body is obtained through ball milling, drying, granulation, screening, and compression molding, and a high-energy storage and high-entropy ceramic dielectric material is obtained through sintering.
[0016] Technical features and effects of the present invention:
[0017] In BaTiO 3 Six A-site cations (K, Na, Bi, Sr, Ca and Mg) were introduced to construct high-entropy ceramics to optimize their energy storage performance. The prepared ceramic dielectric materials were regarded as solid solutions of several perovskite structure compounds.
[0018] In order to ensure the balance and stability of the electronic valence state, the content of barium ions in the A position was fixed at 0.2 mol; the introduction of (K 0.5 Bi 0.5 )TiO 3 As a ferroelectric phase, potassium ions are highly volatile during long-term high-temperature sintering, so the introduction of (Na 0.5 Bi 0.5 )TiO 3 As a supplement, KBT and NBT constitute the ferroelectric phase variables in the distribution ratio of this group.
[0019] In order to ensure a higher dielectric constant, SrTiO3 and CaTiO3 are introduced as non-ferroelectric phases. At the same time, in order to ensure that the dielectric material has high temperature stability, balance the average ion radius of the A position and further enhance its relaxation performance, MgTiO3 is introduced as a supplement, so that STO, MTO and CTO constitute the non-ferroelectric phase variables in this group distribution ratio. Among them (K 0.5 Bi 0.5 )TiO 3 、(Na0.5 Bi 0.5 )TiO 3 and BaTiO 3 The hysteresis loop of ferroelectric ceramics shows the characteristics of high saturation polarization and high remnant polarization; MgTiO 3 、SrTiO 3 and CaTiO 3 Non-ferroelectric ceramics exhibit the characteristics of low saturation polarization and low remnant polarization.
[0020] After the introduction of these components, a relative balance between the ferroelectric phase and the non-ferroelectric phase was achieved. Thanks to the presence of various ions at the A site, the relaxation characteristics were greatly enhanced, resulting in better ferroelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the XRD spectrum of the high entropy ceramic of the present invention;
[0022] Figure 2 The ferroelectric diagrams of Examples 1-5 and Comparative Example 1 at 150-320 kV / cm;
[0023] Figure 3 Graph showing energy storage density and energy storage efficiency of Examples 1-5 and Comparative Example 1 at 150-320 kV / cm. DETAILED DESCRIPTION
[0024] The technical scheme and technical effects of the present invention can be more fully understood through the following embodiments and comparative examples.
[0025] Embodiment 1:
[0026] (1) BaCO 3 (99.95%), K 2 CO 3 (99%), Na 2 CO 3 (99%), Bi 2 O 3 (99.99%), SrCO 3 (99.95%), CaCO 3 (99.99%), MgCO 3 (99.99%) and TiO 2 (99.99%) powder as raw materials, respectively according to the general formula BaTiO 3 、CaTiO 3 、SrTiO 3 MgTiO 3 ,(K 0.5 Bi 0.5 )TiO 3and(Na 0.5 Bi 0.5 )TiO 3 The ingredients were mixed, and then anhydrous ethanol was added respectively to obtain six slurries of BTO, CTO, STO, MTO, KBT and NBT.
[0027] (2) The six slurries were placed in a constant temperature oven at 80°C for drying to remove anhydrous ethanol, and six powders of BTO, CTO, STO, MTO, KBT, and NBT were obtained. The BTO, KBT, and NBT powders were pre-calcined at 800°C under closed conditions, and the STO, CTO, and MTO powders were pre-calcined at 860°C under closed conditions, and the heat preservation time was 3 hours to obtain BTO, KBT, NBT, STO, CTO, and MTO raw materials (perovskite structure).
[0028] (3) Mix the above raw materials according to the mass ratio
[0029] BTO:KBT:NBT:STO:CTO:MTO=0.20:0.08:0.08:0.16:0.16:0.16 are weighed, and an appropriate amount of anhydrous ethanol is added to the powder, and the powder is mixed evenly through secondary ball milling to form a slurry; the ball-milled slurry is dried at 80°C, and a ceramic green body is obtained through granulation, sieving and molding.
[0030] (4) The ceramic body is subjected to a binder removal treatment at 580°C, and the ceramic body after binder removal is sintered at a sintering temperature of 1220°C, a heating rate of 1°C / min, and a holding time of 1 hour. After cooling to room temperature, a perovskite ceramic material is obtained, and its chemical composition is: Ba 0.2 [(K 0.5 Na 0.5 )Bi] 0.16 (SrCaMg) 0.16 TiO 3 .
[0031] (5) The prepared sample was processed into a sheet with smooth surfaces and a thickness of about 0.1 mm, and silver electrodes were plated. Then, its ferroelectric properties were tested at room temperature, and its energy storage density and efficiency were calculated. The energy storage density (W) of the ceramic material under an electric field of 345 kV / cm was rec ) reaches 3.47J / cm 3 , the energy storage efficiency (η) reaches 88.4%. Example 2:
[0032] (1) Same as step (1) of Example 1.
[0033] (2) Same as step (2) of Example 1.
[0034] (3) Raw materials by mass ratio
[0035] BTO:KBT:NBT:STO:CTO:MTO=0.20:0.085:0.085:0.153:0.153:0.153 are weighed, and an appropriate amount of anhydrous ethanol is added to the powder, and the powder is mixed evenly through secondary ball milling to form a slurry; the ball-milled slurry is dried at 80°C, and a ceramic green body is obtained through granulation, sieving and molding.
[0036] (4) The ceramic body is subjected to a binder removal treatment at 580°C, and the ceramic body after binder removal is sintered at a sintering temperature of 1220°C, a heating rate of 1°C / min, and a holding time of 1 hour. After cooling to room temperature, a perovskite ceramic material is obtained, and its chemical composition is: Ba 0.2 [(K 0.5 Na 0.5 )Bi] 0.17 (SrCaMg) 0.153 TiO 3 .
[0037] (5) The prepared sample was processed into a sheet with smooth surfaces and a thickness of about 0.1 mm, and silver electrodes were plated. Then, its ferroelectric properties were tested at room temperature, and its energy storage density and efficiency were calculated. The energy storage density (W) of the ceramic material under an electric field of 325 kV / cm was rec ) reaches 3.80J / cm 3 , the energy storage efficiency (η) reaches 87.7%.
[0038] Embodiment 3:
[0039] (1) Same as step (1) of Example 1.
[0040] (2) Same as step (2) of Example 1.
[0041] (3) Raw materials by mass ratio
[0042] BTO:KBT:NBT:STO:CTO:MTO=0.20:0.09:0.09:0.1467:0.1467:0.1467 are weighed, and an appropriate amount of anhydrous ethanol is added to the powder, and the powder is mixed evenly through secondary ball milling to form a slurry; the ball-milled slurry is dried at 80°C, and a ceramic green body is obtained through granulation, sieving and molding.
[0043] (4) The ceramic body is subjected to a binder removal treatment at 580°C, and the ceramic body after binder removal is sintered at a sintering temperature of 1220°C, a heating rate of 1°C / min, and a holding time of 1 hour. After cooling to room temperature, a perovskite ceramic material is obtained, and its chemical composition is: Ba 0.2 [(K 0.5 Na 0.5 )Bi] 0.18 (SrCaMg)0.1467 TiO 3 .
[0044] (5) The prepared sample was processed into a sheet with smooth surfaces and a thickness of about 0.1 mm, and silver electrodes were plated. Then, its ferroelectric properties were tested at room temperature, and its energy storage density and efficiency were calculated. The energy storage density (W) of the ceramic material under an electric field of 320 kV / cm was rec ) reaches 4.35J / cm 3 , the energy storage efficiency (η) reaches 89.5%.
[0045] Embodiment 4:
[0046] (1) Same as step (1) of Example 1.
[0047] (2) Same as step (2) of Example 1.
[0048] (3) Raw materials by mass ratio
[0049] BTO:KBT:NBT:STO:CTO:MTO=0.20:0.095:0.095:0.14:0.14:0.14 are weighed, and an appropriate amount of anhydrous ethanol is added to the powder, and the powder is mixed evenly through secondary ball milling to form a slurry; the ball-milled slurry is dried at 80°C, and a ceramic green body is obtained through granulation, sieving and molding.
[0050] (4) The ceramic body is subjected to a binder removal treatment at 580°C, and the ceramic body after binder removal is sintered at a sintering temperature of 1220°C, a heating rate of 1°C / min, and a holding time of 1 hour. After cooling to room temperature, a perovskite ceramic material is obtained, and its chemical composition is: Ba 0.2 [(K 0.5 Na 0.5 )Bi] 0.19 (SrCaMg) 0.14 TiO 3 .
[0051] (5) The prepared sample was processed into a sheet with smooth surfaces and a thickness of about 0.1 mm, and silver electrodes were plated. Then, its ferroelectric properties were tested at room temperature, and its energy storage density and efficiency were calculated. The energy storage density (W) of the ceramic material under an electric field of 200 kV / cm was rec ) reaches 3.48J / cm 3 , the energy storage efficiency (η) reaches 83.8%.
[0052] Embodiment 5:
[0053] (1) Same as step (1) of Example 1.
[0054] (2) Same as step (2) of Example 1.
[0055] (3) Raw materials by mass ratio
[0056] BTO:KBT:NBT:STO:CTO:MTO=0.20:0.10:0.10:0.133:0.133:0.133 are weighed, and an appropriate amount of anhydrous ethanol is added to the powder, and the powder is mixed evenly through secondary ball milling to form a slurry; the ball-milled slurry is dried at 80°C, and a ceramic green body is obtained through granulation, sieving and molding.
[0057] (4) The ceramic body is subjected to a binder removal treatment at 580°C, and the ceramic body after binder removal is sintered at a sintering temperature of 1220°C, a heating rate of 1°C / min, and a holding time of 1 hour. After cooling to room temperature, a perovskite ceramic material is obtained, and its chemical composition is: Ba 0.2 [(K 0.5 Na 0.5 )Bi] 0.20 (SrCaMg) 0.133 TiO 3 .
[0058] (5) The prepared sample was processed into a sheet with smooth surfaces and a thickness of about 0.1 mm, and silver electrodes were plated. Then, its ferroelectric properties were tested at room temperature, and its energy storage density and efficiency were calculated. The energy storage density (W) of the ceramic material under an electric field of 175 kV / cm was rec ) reaches 3.25J / cm 3 , the energy storage efficiency (η) reaches 81.9%. Comparative Example 1:
[0059] (1)BaCO 3 (99.95%) and TiO 2 (99.99%) powder as raw material, according to the general formula BaTiO 3 The ingredients are prepared, and then anhydrous ethanol is added respectively to obtain a slurry.
[0060] (2) The obtained slurry was placed in a constant temperature oven at 80° C. for drying to remove anhydrous ethanol, thereby obtaining four powders. The BTO powders were pre-sintered at 800° C. in a sealed condition for 3 hours to obtain a BTO (perovskite structure) raw material.
[0061] (3) adding an appropriate amount of anhydrous ethanol to the powder, and performing secondary ball milling to mix the powder evenly to form a slurry; drying the slurry after ball milling at 80° C., and obtaining a ceramic green body through granulation, sieving, and molding.
[0062] (4) The ceramic body is subjected to a binder removal treatment at 580°C, and the ceramic body after binder removal is sintered at a sintering temperature of 1220°C, a heating rate of 1°C / min, and a holding time of 1 hour. After cooling to room temperature, a perovskite ceramic material is obtained, and its chemical composition is: BaTiO 3 .
[0063] (5) The prepared sample was processed into a sheet with smooth surfaces and a thickness of about 0.1 mm, and silver electrodes were plated. Then, its ferroelectric properties were tested at room temperature, and its energy storage density and efficiency were calculated. The energy storage density (W) of the ceramic material under an electric field of 150 kV / cm was rec ) reaches 2.78J / cm 3 , the energy storage efficiency (η) reaches 72.8%.
[0064] Sample performance test:
[0065] Figure 1 Yes 0.2 [(K 0.5 Na 0.5 )Bi] x (SrCaMg) (2 / 3)(0.4-x) TiO 3 From the XRD curve of the high entropy ceramic material, it can be seen that the peak positions of the samples with different contents are almost completely overlapped, indicating that all elements have entered the lattice site and present a single-phase perovskite structure. The local magnified image shows that the (110) peak moves to a lower angle as x increases, indicating that its grain size increases with the increase in the proportion of the ferroelectric phase content.
[0066] Figure 2 It is the ferroelectric diagram of Examples 1-5 and Comparative Example 1. As the proportion of ferroelectric phase content increases, the PE curve of the ceramic shows regular changes, the saturation polarization intensity increases, the residual polarization intensity increases, the breakdown field strength decreases, and the hysteresis loop becomes thicker.
[0067] Figure 3 The energy storage density and energy storage efficiency change curves of Examples 1-5 and Comparative Example 1 show that as the proportion of the ferroelectric phase increases, the energy storage efficiency shows an overall downward trend, while the energy storage density increases first and then decreases. This is because the increase in the proportion of the ferroelectric phase is accompanied by an increase in the saturation polarization intensity and an increase in the residual polarization intensity. When the proportion of the ferroelectric phase is small, this effect promotes the increase in energy storage density. When the proportion of the ferroelectric phase is large, this effect increases the leakage current of the sample, resulting in a decrease in energy storage density. Preferably, the sample with x=0.18 maintains a good energy storage efficiency while obtaining a higher energy storage density.
Claims
1. A high energy storage and high entropy ceramic dielectric material, characterized in that: The chemical composition of the high energy storage and high entropy ceramic dielectric material is: Ba 0.2 [(K 0.5 Na 0.5 )Bi] x (SrCaMg) (2 / 3)(0.4-x) TiO3; x = 0.16-0.
20.
2. The high energy storage and high entropy ceramic dielectric material according to claim 1, wherein the preparation method comprises the following steps: (1) BaCO3, K2CO3, Na2CO3, Bi2O3, SrCO3, CaCO3, MgCO3 and TiO2 powders were used as raw materials, and the general formulas of BaTiO3, CaTiO3, SrTiO3, MgTiO3, (K 0.5 Bi 0.5 )TiO3 and (Na 0.5 Bi 0.5 )TiO3 ingredients, and then add anhydrous ethanol to prepare the slurry, mix the powders evenly by ball milling, dry, remove the anhydrous ethanol, and obtain BaTiO3, CaTiO3, SrTiO3, MgTiO3, (K 0.5 Bi 0.5 )TiO3 and (Na 0.5 Bi 0.5 )TiO3 powder; (2) Under closed conditions, CaTiO3, SrTiO3 and MgTiO3 powders were pre-sintered at 860°C, and BaTiO3, (K 0.5 Bi 0.5 )TiO3 and (Na 0.5 Bi 0.5 ) TiO3 powder is pre-calcined at 800°C to obtain CTO, STO, MTO, BTO, KBT and NBT raw materials; (3) The above CTO, STO, MTO, BTO, KBT and NBT raw materials are weighed according to the following mass ratio: BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.16±10%):(0.16±10%):(0.16±10%):(0.08±10%):(0.08±10%); Or BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.153±10%):(0.153±10%):(0.153±10%):(0.085±10%):(0.085±10%); Or BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.1467±10%):(0.1467±10%):(0.1467±10%):(0.09±10%):(0.09±10%); Or BTO:STO:CTO:MTO:KBT:NBT = (0.20 ± 10%): (0.14 ± 10%): (0.14 ± 10%): (0.14 ± 10%): (0.095 ± 10%): (0.095 ± 10%); Or BTO:STO:CTO:MTO:KBT:NBT=(0.20±10%):(0.133±10%):(0.133±10%):(0.133±10%):(0.10±10%):(0.10±10%); Then, anhydrous ethanol is added respectively, and ceramic green bodies are obtained through ball milling, drying, granulation, screening and compression molding, and high energy storage and high entropy ceramic dielectric materials are obtained through sintering.
Citation Information
Patent Citations
Method of increasing property of bismuth sodium titanate base lead-free piezoelectric ceramic
CN101058505A
Unleaded ceramic with high voltage and high energy density simultaneously and preparation method for unleaded ceramic
CN104710174A
High-energy-storage non-equimolar-ratio high-entropy perovskite oxide ceramic material and preparation method thereof
CN114085079A
High-entropy ceramic material with high energy storage density and preparation method thereof
CN114621004A
High-entropy perovskite oxide doped ceramic, preparation method and application thereof
CN115991599A